EFEK HIPOTERMIA SEBAGAI NEUROPROTEKTIF PADA STROKE ISKEMIK - Chandra Wirawan; Shierly Shierly (PERDOSNI, 2020)
The incidence of stroke has been increasing continuously. It is found that a higher prevalence of ischemic stroke than the prevalence of hemorrhagic stroke and the disability of stroke is the highest of all other diseases. Many methods of therapeutic hypothermia can be done locally (in body surface or lesion) and systemically (endovascular). Based on various randomized controlled trial (RCT) studies, therapeutic hypothermia can provide neuroprotective effect by reducing brain metabolism, decreasing free radical, inhibiting inflammatory response and preventing neuron cell apoptosis so that the level of the disability can be lower. Key Words: Ischemic stroke, neuroprotective, reperfusion, therapeutic hypothermia